PENGARUH SIKAP MAHASISWA MUSLIM TERHADAP MINAT PADA BANK SYARIAH - Agus Arwani (IAIN Pekalongan, 2015)
This study has two objectives, namely 1) understanding moslem students attitudes toward Islamic banks products in Yogyakarta, and 2) determining the interest groups of students majoring in Islamic economics / muamalah in Yogyakarta on Islamic Banking. Data were collected through questionnaires and tested by regression analysis. The results showed that the attitude and subjective norms affect the interest savings in Islamic banks. This means that all independent variables have a significant positive relationship with the dependent variable.